Numerical modelling of bulk superconductor magnetisation - Ainslie, Mark; Fujishiro, Hiroyuki (Professor of materials science and engineering) (IOP ebooks. 2020 collection., 2020)
This book provides readers with numerical analysis techniques to model the magnetisation of bulk superconductors based on the finite element method. Applications of magnetised bulk superconductors are wide ranging in engineering due to their greatly enhanced magnetic field compared to conventional magnets. Their uses include rotating electric machines, magnetic resonance imaging (MRI), nuclear magnetic resonance (NMR) systems and magnetic separation. Numerical modelling is a particularly important and cost-effective method to guide both superconducting material processing and practical device design. It has been used successfully to interpret experimental results and the physical behaviour and properties of bulk superconductors during their various magnetisation processes, to predict and propose new magnetisation techniques and to design and predict the performance of bulk superconductor-based devices. The book provides the necessary fundamentals of bulk superconducting materials, how to model these and their various magnetisation processes and an in-depth summary of the current state-of-the-art in the field. Throughout the book, example models, implemented in the software package COMSOL Multiphysics®, are provided so that readers may carry out modelling of their own. The current state-of-the-art in modelling bulk superconductors is summarised, including case studies that highlight the usefulness of such models.